DIGITAL CULTURAL ACCULTURATION AND DA’WAH ETHICS: THE ETHICAL DILEMMA OF INTERGENERATIONAL COMMUNICATION BETWEEN PARENTS AND CHILDREN - Raenita Dwimulya Tahir; Alem Febri Sonni; Muliadi Mau (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
Technological advances in the digital age have brought significant changes in the communication patterns between parents and children, especially in Islamic preaching. Children often feel that such surveillance intrudes on their privacy, creating tension in interpersonal relationships. This study examines the ethical dilemmas faced by parents, especially regarding the supervision of children's digital activities in the digital era. Using a descriptive qualitative approach, through interviews with 50 participants consisting of 30 parents and 20 children, it was found that most parents feel the need to monitor their children's digital activities to protect them from various risks, including cyber bullying and exposure to negative content. The findings of this study emphasise the urgency of improving digital literacy for parents and children, as well as the need to integrate Islamic values in parenting. The principle of amar ma'ruf nahi munkar serves as a guideline in building more open communication, thereby reducing conflict and strengthening mutual trust. In addition, the study revealed challenges in implementing this approach, highlighting the need for support from educational institutions and communities in providing adequate resources for parents. The conclusions of this study emphasise the importance of balancing the protection and respect of children's rights, so that parents can function as advocates for their children's development in the digital age, without neglecting moral and ethical values.